Law Enforcement against Children as Perpetrators of Victim Blaming in Sexual Violence Cases - Pinta Prasetyaning Darma Fitri; Rini Fathonah; Gidayani; Fristia Berdian Tamza (Istinbath : Jurnal Hukum, 2025)
This study critically examines the phenomenon of children as perpetrators of victim blaming in cases of sexual violence. This dimension has received only a small portion of attention in legal and child protection policy studies. Using an empirical legal approach that combines normative analysis, case studies, and conceptual analysis, this study evaluates the effectiveness of the law enforcement system against children involved in blaming victims of sexual violence. The findings show that although there is a fairly progressive legal framework through Law Number 11 of 2012 concerning the Criminal Justice System for Children, its implementation has not substantively addressed the symbolic aspects of violence. First, legal narratives tend to place children as perpetrators in general, without considering the socio-cultural context behind victim blaming. Second, the penal system remains textual and lacks a rehabilitative approach consistent with restorative justice principles. Third, diversion mechanisms have not been optimized to address child perpetrators in cases of victim blaming as non-physical violence. Fourth, the weak literacy of law enforcement officials regarding the psychosocial and symbolic dimensions of violence results in responses that are procedural and non-transformative. This study suggests reinforcing legal interventions based on moral education, social recovery, and cross-sectoral involvement to prevent the replication of symbolic violence by children in their social spaces.